2012
DOI: 10.1093/brain/awr321
|View full text |Cite
|
Sign up to set email alerts
|

Severe olfactory dysfunction is a prodromal symptom of dementia associated with Parkinson's disease: a 3 year longitudinal study

Abstract: Dementia is one of the most debilitating symptoms of Parkinson's disease. A recent longitudinal study suggests that up to 80% of patients with Parkinson's disease will eventually develop dementia. Despite its clinical importance, the development of dementia is still difficult to predict at early stages. We previously identified olfactory dysfunction as one of the most important indicators of cortical hypometabolism in Parkinson's disease. In this study, we investigated the possible associations between olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
169
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(190 citation statements)
references
References 39 publications
16
169
3
2
Order By: Relevance
“…Several additional clinical observations support the strong negative prognostic value of posterior cortical hypometabolism. For example, recent longitudinal studies demonstrated that visual hallucinations and hyposmia, which coincided with a marked temporoparietal and occipital hypometabolism in PD (with or without MCI), were associated with an increased conversion to PDD (104,105). Likewise, PD patients with the rapid-eye-movement sleep behavior disorder showed lower cognitive performance and a higher likelihood of MCI and posterior cortical hypometabolism than did PD patient without this disorder (106).…”
Section: F-fdg Pet Imaging Of Cognitive Impairment In Pdmentioning
confidence: 99%
“…Several additional clinical observations support the strong negative prognostic value of posterior cortical hypometabolism. For example, recent longitudinal studies demonstrated that visual hallucinations and hyposmia, which coincided with a marked temporoparietal and occipital hypometabolism in PD (with or without MCI), were associated with an increased conversion to PDD (104,105). Likewise, PD patients with the rapid-eye-movement sleep behavior disorder showed lower cognitive performance and a higher likelihood of MCI and posterior cortical hypometabolism than did PD patient without this disorder (106).…”
Section: F-fdg Pet Imaging Of Cognitive Impairment In Pdmentioning
confidence: 99%
“…81 It has been reported that patients with severe hyposmia have an 18-fold increase in the risk for dementia within 3 years. 82 Another frequent and important premotor feature is RBD. Kang et al assessed the combined effect of RBD and hyposmia on cognition and motor phenotype.…”
Section: Clinical Correlates Of Olfactory Impairment In Pd Smell and mentioning
confidence: 99%
“…Consistent with prior studies, age, greater motor severity, presence of RBD symptoms, and worse olfaction at baseline predicted future cognitive decline. [30][31][32][33][34][35] These findings suggest that early diffuse brainstem pathology, widespread PD pathology, or comorbid pathology that occurs with aging might contribute to initial cognitive decline in PD.…”
mentioning
confidence: 91%